Job security, stability, and production efficiency. Issue 1 (January 2017) - Fu, Hu; Kleinberg, Robert D.; Lavi, Ron; Smorodinsky, Rann
Abstract : We study a two‐sided matching market with a set of heterogeneous firms and workers in an environment where jobs are secured by regulation. Without job security Kelso and Crawford have shown that stable outcomes and efficiency prevail when all workers are gross substitutes to each firm. It turns out that by introducing job security, stability and efficiency may still prevail, and even for a significantly broader class of production functions.